Affect of pouring temperature on volume deficit of US 413 - Santhi, Samavedam (International Journal of Computer Sciences and Engineering, 2025)
US 413 (Al-12Si) alloy volume deficit characteristic has been studied in this paper. Influence of pouring temperature on volume deficit is studied and latter is addition of Macro cavities, Internal porosity, Surface sink and Volumetric contraction. The decrease in definite volume of molten metal leads to volume deficit in castings, and it can be envisaged as a casting defect. Volume deficit of a casting depends on casting material and casting conditions. Influence of pouring temperature and casting shape on the volume deficit characteristics are studied in this paper. Increase in pouring temperature lowers the rate of heat extraction by the mould thereby reducing volume deficit.